Pancreas—Its Functions, Disorders, and Physiological Impact on the Mammals’ Organism - Karpińska, Monika; Czauderna, Marian (Frontiers in Physiology, 2022)
This review aimed to analyse the scientific literature on pancreatic diseases (especially exocrine pancreatic insufficiency). This review also describes the correlation between the physiological fitness of the pancreas and obesity. The influence of the pancre-atic exocrine function on the development of the organism of adults and adolescents was also described. The results of piglet studies available in the literature were cited as an established model used to optimise treatments for pancreatic diseases in hu-mans. The pancreas has an exocrine and hormonal function. Consequently, it is one of the key internal organs in animals and humans. Pancreatic diseases are usually severe and particularly troublesome. A properly composed diet and taken dietary sup-plements significantly improve the patient's well-being, as well as the course of the disease. Therefore, a diet and a healthy life-style positively affect maintaining the optimal physiological efficiency of the pancreas.